Parathyroid gland volume as one of the indicators for parathyroidectomy in secondary hyperparathyroidism - Yee, Ho Kah (2018)
Background Secondary hyperparathyroidism occurs as a result of the failure of the kidneys to provide adequate calcium and phosphate homeostasis in chronic kidney disease. In the long run, there are other associated disorders of bone metabolism that follows, leading to incapacitating disabilities. Treatment of secondary hyperparathyroidism is centered around the control of hyperphosphatemia and hypocalcemia, and this can be achieved by medical therapy or surgery to remove the parathyroid glands. This study aims to determine the volume of the parathyroid gland in relation to its degree of hyperplasia, and subsequently to use the volume of the parathyroid gland as an indicator for parathyroidectomy. Methods This is a case control study conducted in Hospital Queen Elizabeth II, Kota Kinabalu, Sabah. It involves patients with end stage renal disease on dialysis, who have undergone parathyroidectomy for secondary hyperparathyroidism from 1st January 2012 until 31st December 2017. The study includes all patients who have undergone parathyroidectomy in the study period, and excludes patients with primary hyperparathyroidism, patients with incomplete biochemical markers prior to surgery, and those with incomplete documentation of histopathological results. The data is thenanalyzed and results generated using Statistical Package for the Social Sciences (SPSS) software version 24 . Results 56 patients who had undergone parathyroidectomy for secondary hyperparathyroidism were studied. We noted poor results with ultrasonography on detection of parathyroid glands in our setting. There was no significant relationship between the actual volume of the parathyroid gland as seen on histopathological examination, or the volume on ultrasound with the degree of hyperplasia of the gland. There was also no significant relationship between the preoperative iPTH levels an the size of the gland nor the degree of hyperplasia of the gland. Conclusion The volume of the parathyroid gland should not be used as the sole indicator of parathyroidectomy. While ultrasound is useful as a non-invasive assessment of the response to medical therapy, we failed to demonstrate the significance of the volume of the gland with the degree of hyperplasia, which reflects on its response to medical therapy. Therefore we suggest that other parameters such as preoperative iPTH levels and symptoms of mineral bone disorders should be taken into consideration prior to parathyroidectomy.